The Influence of Tax Avoidance and Tax Risk on Debt Costs in Property and Real Estate Sector Companies Listed on the Indonesia Stock Exchange - Manalu, Deni Srywahyuni; Loupatty, Linda Grace (Institut Bisnis dan Informatika Kesatuan, 2024)
This study aims to empirically test the effect of tax avoidance and tax risk on debt costs in property and real estate sector companies listed on the Indonesia Stock Exchange. The research used a quantitative approach with secondary data in the form of financial reports presented by the company as a basis for collecting data. The population in this study were property and real estate sector companies listed on the Indonesia Stock Exchange with reports that became research data for the period 2019-2022 with a total population of 91 companies. The sampling method used was purposive sampling with the criteria of companies that had been listed and had not experienced losses during the research year and there were 21 companies. This study uses Descriptive Statistical Tests, then Classical Assumption Tests, then continued with Hypothesis Tests. The results of this study indicate that tax avoidance has a positive and significant effect on debt costs, tax risk also has a significant negative effect on debt costs.